The Influence of Teacher Professionalism and Creativity on Student Motivation in Madrasah Ibtidaiyah - Setyorini, Endah Tri; Khuriyah, Khuriyah (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The goal to be achieved in this study is to determine the effect of teacher professionalism and teacher creativity on student motivation at MIM Plumbon Eromoko Wonogiri. The research used in this research is quantitative research with multiple linear regression models. The research data was conducted by distributing questionnaires to 97 students consisting of grades 4, 5, and 6 at MIM Plumbon. The results of the analysis show that there is an influence of teacher professionalism and teacher creativity on student learning motivation at MIM Plumbon. This is evidenced by the coefficient of determination of 0.039 which states that 3.9% of the variation that occurs in student learning motivation can be explained by teacher professionalism and teacher creativity. The remaining 96.1% of the variation in student learning motivation can be explained by factors outside the research such as students' aspirations, student learning interests, student abilities, student learning conditions, parental attention, parental support, learning facilities, peer interactions, and so on. Thus it can be concluded that there is a significant influence of teacher professionalism and teacher creativity on student learning motivation at MIM Plumbon Eromoko Wonogiri.